PENGARUH HARI PERDAGANGAN TERHADAP RETURN SAHAM (PENGUJIAN THE DAY OF THE WEEK, WEEK-FOUR EFFECT, DAN ROGALSKI EFFECT) PADA PERUSAHAAN KEUANGAN DI BURSA EFEK INDONESIA PERIODE 2017 - Rizki Khoiri; Deny Ismanto (Universitas Ahmad Dahlan, 2019)
This study aims to examine (1) the difference in average daily return in one week (2) test the occurrence of negative returns on the fourth and fifth weeks of Monday on financial sector stock returns on the Indonesia Stock Exchange in the period 2017 and (3) test whether a positive return and tends to be larger than other months on Monday in April. The population in this study were financial sector companies listed on the Indonesia Stock Exchange. Samples were taken by purposive sampling method. Samples consisted of 6 financial sector companies listed on the Indonesia Stock Exchange and included in LQ45 during the 2017 period. The results of data analysis show that trading days have no significant effect on stock returns. There is no negative return on the fourth and fifth week of Monday on stock returns and positive returns are found and tend to be greater than the other months on Monday in April on financial sector stock returns on the Indonesia Stock Exchange in the 2017 period.